Intelligent Routines II Solving Linear Algebra and Differential Geometry with Sage - Anastassiou, George A.; Iatan, Iuliana F.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
“Intelligent Routines II: Solving Linear Algebra and Differential Geometry with Sage” contains numerous of examples and problems as well as many unsolved problems. This book extensively applies the successful software Sage, which can be found free online http://www.sagemath.org/. Sage is a recent and popular software for mathematical computation, available freely and simple to use. This book is useful to all applied scientists in mathematics, statistics and engineering, as well for late undergraduate and graduate students of above subjects. It is the first such book in solving symbolically with Sage problems in Linear Algebra and Differential Geometry. Plenty of SAGE applications are given at each step of the exposition.
Vector Spaces -- Plane And Straight Line In E -- Linear Transformations -- Euclidean Vector Spaces -- Bilinear And Quadratic Forms -- Differential Geometry Of Curves And Surfaces.
Keywords: Computational intelligence; Computer mathematics; Mathematical analysis; Analysis (Mathematics).; Computational Intelligence; Computational Mathematics and Numerical Analysis; Analysis